Strategic Analysis of Village Government Performance In Governance: Study in Kalirejo Village, Probolinggo Regency, Indonesia - Wanusmawatie, Ike; Fatimah Durrety, Shinta; Johan Ferdhianzah, Hefry; Rohmatul Khasanah, Ulvi (Universitas Negeri Surabaya, 2024)
The purpose of this study is to describe and examine the Kalirejo Village Government's performance in governance. This study employs SWOT analysis with the Analytical Hierarchy Process (AHP) to identify strategic internal and external elements. The research method used was qualitative. According to the study's findings, administrative services dominate village government performance. These services are intermediary in nature, connecting the village community's needs to the regional government, which owns the local public service authority. Second, transparency, accountability, and participation are more of a formality when reporting to the superior authority, specifically the regency. Third, in order to improve village government performance in the short term, standard operating procedures for administrative services must be developed. Furthermore, as a medium-term strategy, infrastructure development and connection with the village council, as well as collaboration with third parties, will be implemented to boost competency and service efficiency. It is hoped that this strategic decision-making will be sustainable and effective in village governance, thereby enhancing the quality of services and the well-being of village communities in the future